A microfluidic chip carrier including temperature control and perfusion system for long-term cell imaging. (October 2021) - Cantoni, Federico; Werr, Gabriel; Barbe, Laurent; Porras, Ana Maria; Tenje, Maria
Graphical abstract: Abstract: Microfluidic devices are widely used for biomedical applications but there is still a lack of affordable, reliable and user-friendly systems for transferring microfluidic chips from an incubator to a microscope while maintaining physiological conditions when performing microscopy. The presented carrier represents a cost-effective option for sustaining environmental conditions of microfluidic chips in combination with minimizing the device manipulation required for reagent injection, media exchange or sample collection. The carrier, which has the outer dimension of a standard well plate size, contains an integrated perfusion system that can recirculate the media using piezo pumps, operated in either continuous or intermittent modes (50–1000 µl/min). Furthermore, a film resistive heater made from 37 µm-thick copper wires, including temperature feedback control, was used to maintain the microfluidic chip temperature at 37 °C when outside the incubator. The heater characterisation showed a uniform temperature distribution along the chip channel for perfusion flow rates up to 10 µl/min. To demonstrate the feasibility of our platform for long term cell culture monitoring, mouse brain endothelial cells (bEnd.3) were repeatedly monitored for a period of 10 days, demonstrating a system with both the versatility and the potential for long imaging in microphysiological system cell cultures.